Literature between two worlds : the first fifty years of the Xhosa novel and poetry - Zotwana, Sydney Zanemvula (African Languages and Literatures, 2016)
The main preoccupation in this thesis is to illustrate that, although there is no doubt that the missionaries deserve all the praise that they have been showered with, for their role in the development of Xhosa literature, there is a sense in which they can be said to have contributed as much also to its underdevelopment. It is my view that Xhosa literature has had a very unfortunate history, because of having an origin that is located in the history of Christianization. This history has haunted Xhosa literary creativity from its early beginnings to the present. The success of the mission to convert them to Christianity was anchored on the principle of total alienation of the Xhosa from their world-view: from their culture, from their religion, from their chiefs, from their literary art, and even from their homes. The intention was to turn them into new beings - Christian and loyal subjects of the British Crown - and to make them not only reject, but also despise their past. Therefore Western-style education for the Blacks in South Africa did not come out of any sense of altruism on the part of those by whom it was introduced. It was the interests of its initiators and their country that had to be served by the education of the Blacks. It was in this context that Xhosa literature was born. It was produced to promote the interests of the Christian church and therefore those of the British Crown. Its production was controlled by the missionaries, the owners of the publishing houses, but it was produced by the Christian and literate Xhosa most of whom had studied in mission schools. It was produced to crush the past and any aspirations that were in conflict with those of the Christian church and the British imperial designs. In short, it was a literature against its people. However, the Christian and literate Xhosa was never accepted as the equal of the other British subjects who were White. He was excluded from all law-making mechanisms and was affected by the many Native Laws that were passed, as badly as his non-Christian brothers and sisters. He witnessed land dispossession and all the other atrocities perpetrated by White rulers. His literary art had been harnessed to legitimize and perpetrate this situation and he dared not use his art to change it. It is in the light of this context that this thesis contends that Xhosa literature is between two worlds. It is argued that Xhosa literature, because of the writers' dilemma created by their position between these two conflicting universes, has been forced to be mute in the face of the Black people's experiences of oppression, and therefore to be indifferent to the Black people's struggles to resist colonization and to liberate themselves from this oppression. It is however, pointed out that some works are characterised by the writers' attempts to grapple with this dilemma. Finally this thesis advocates complete liberation of literary artists from state control, indirect though it may be, and also a change in the teaching and analysis of Xhosa literature.